2015
DOI: 10.1530/eje-14-1157
|View full text |Cite
|
Sign up to set email alerts
|

GH signaling in human adipose and muscle tissue during ‘feast and famine’: amplification of exercise stimulation following fasting compared to glucose administration

Abstract: Objective: Fasting and exercise stimulates, whereas glucose suppresses GH secretion, but it is uncertain how these conditions impact GH signaling in peripheral tissues. To test the original 'feast and famine hypothesis' by Rabinowitz and Zierler, according to which the metabolic effects of GH are predominant during fasting, we specifically hypothesized that fasting and exercise act in synergy to increase STAT-5b target gene expression. Design and methods: Eight healthy men were studied on two occasions in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Consistent with previous human studies [6], [7], [8], [9], [10], [11], we recorded STAT5 phosphorylation in AT 60 min after the GH bolus together with upregulated gene expression of IGF-1 and CISH . JAK2-STAT5 signaling is considered the dominant GH signaling pathway [44], and studies in adipocyte-specific STAT5 and JAK2 knockout mice imply that the JAK2-STAT5 pathway also mediates GH-induced lipolysis [12], [45].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous human studies [6], [7], [8], [9], [10], [11], we recorded STAT5 phosphorylation in AT 60 min after the GH bolus together with upregulated gene expression of IGF-1 and CISH . JAK2-STAT5 signaling is considered the dominant GH signaling pathway [44], and studies in adipocyte-specific STAT5 and JAK2 knockout mice imply that the JAK2-STAT5 pathway also mediates GH-induced lipolysis [12], [45].…”
Section: Discussionsupporting
confidence: 91%
“…This temporal pattern suggests that the effect involves regulation of gene expression in AT. We have consistently demonstrated that systemic GH acutely activates the STAT5 signaling pathway, which is considered the canonical pathway whereby GH regulates transcription of target genes [5], in human AT in vivo [6], [7], [8], [9], [10], [11]. In support of this, studies in rodents indicate that STAT5 is involved in GH-induced lipolysis [12], [13], [14], [15], but there are also in vitro studies to suggest that GH stimulates lipolysis via activation of the MAPK pathway [16], [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARG polymorphisms may be involved in the growth hormone/STAT5B pathway [35], and mice that were deficient in members of this pathway developed craniofacial abnormalities [30]. The growth hormone/STAT5B pathway also plays an important role in regulating energy metabolism in adipose and muscle tissue, suggesting that PPARG may cause craniofacial abnormalities and dysfunction of adipose and muscle tissue metabolism through this pathway [36,37]. In addition, the rs1801282 SNP is located in an exon and is a missense variant that affects the amino acid sequence of the PPARG protein (Pro12Ala).…”
Section: Discussionmentioning
confidence: 99%
“…This hormone plays an important role in the regulation of anabolism and in the preservation of lean mass, and some of these anabolic effects are mediated by stimulation of lipolysis. Studies in humans have shown that GH reduces protein breakdown by about 30% during fasting, and this effect depends on the mobilization of free fatty acids from lipid stores [10].…”
Section: Gh/igf-1 Axismentioning
confidence: 99%